ダイ35ジ ナンキョク チイキ カンソクタイ キショウ ブモン ホウコク 1994 - 稲川, 譲; イナガワ, ユズル; 山本, 義勝; ヤマモト, ヨシカツ; 田口, 雄二; タグチ, ユウジ; 阿保, 敏広; アボ, トシヒロ; 居島, 修; イジマ, オサム; Inagawa, Yuzuru; Yamamoto, Yoshikatsu; et al. (1997)
P(論文) この報告は第35次南極地域観測隊気象部門が, 1994年2月1日から1995年1月31日まで昭和基地において行った気象観測の結果をまとめたものである。観測方法, 設備, 結果の取り扱い等は第34次観測隊とほぼ同じである。越冬期間中特記される気象としては, 次のものがあげられる。1)昭和基地ではブリザードの襲来が28回, 日数では60日でほぼ平年並みであった。2)6年連続でオゾンホールを観測し, 日代表値では9月27日のオゾン全量が134m atm-cmと観測開始以来最低値を記録した。 This paper describes the results of meteorological observations carried out by the Meteorological Observation Team of the 35th Japanese Antarctic Research Expedition (JARE-35) from 1 February 1994 to 31 January 1995 at Syowa Station. The method of observations, instruments, and statistics at Syowa Station were the same as those of the JARE-34 observation team. The principal characteristics in the period of JARE-35 are as follows. 1) Blizzards at Syowa Station were encountered twenty-eight times spanning sixty days both of which are normal. 2) The Antarctic ozone hole was observed for six successive years. The lowest value of daily representative total ozone was 134m atm-cm on 27 September. Which was the lowest value in the historical record of Syowa Station. departmental bulletin paper